2023
DOI: 10.3389/fnins.2023.1136790
|View full text |Cite
|
Sign up to set email alerts
|

Resting-state abnormalities in functional connectivity of the default mode network in migraine: A meta-analysis

Abstract: Migraine—a disabling neurological disorder, imposes a tremendous burden on societies. To reduce the economic and health toll of the disease, insight into its pathophysiological mechanism is key to improving treatment and prevention. Resting-state functional magnetic resonance imaging (rs-fMRI) studies suggest abnormal functional connectivity (FC) within the default mode network (DMN) in migraine patients. This implies that DMN connectivity change may represent a biomarker for migraine. However, the FC abnormal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 106 publications
0
3
0
Order By: Relevance
“…This result emphasizes the importance of attentional processing of visual information and sensory neurocircuits for nondrug cues with reward properties in patients with migraines. Resting state functional magnetic resonance studies found that activity in the occipital lobe was significantly impaired in the patient group, and the activity intensity in the occipital lobe decreased significantly when patients processed visual stimulus information (Hu et al., 2023 ; Lee et al., 2023 ). These results may elucidate the pathology of gain and loss processing in patients with migraine.…”
Section: Discussionmentioning
confidence: 99%
“…This result emphasizes the importance of attentional processing of visual information and sensory neurocircuits for nondrug cues with reward properties in patients with migraines. Resting state functional magnetic resonance studies found that activity in the occipital lobe was significantly impaired in the patient group, and the activity intensity in the occipital lobe decreased significantly when patients processed visual stimulus information (Hu et al., 2023 ; Lee et al., 2023 ). These results may elucidate the pathology of gain and loss processing in patients with migraine.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent study examined a large sample suffering from migraine with aura and did not find any resting state differences between patients and controls and the meta-analysis performed by (Chen et al, 2022) did not find consistent FC differences. Nevertheless, another recent meta-analysis focused only on the DMN found significant interictal differences compared to healthy controls (Hu et al, 2023). Considering the prevalence of menstrual-related migraine and the fact that most studies have considerably larger percentage of female participants, some inconsistencies may be due to inadequate control of hormonal factors.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, this study focuses on Default Mode Networks (DMN) -critical brain networks that are most active during rest and are involved in self-referential and introspective ac-tivities. Their relevance spans across various neuropsychological disorders and cognitive functions, serving as a focal point in understanding the neural basis of these conditions and their potential therapeutic targets [4], [5]. DMNs are a subset of Resting-State Networks (RSNs).…”
Section: Introductionmentioning
confidence: 99%